'COVID waste' and social media as method: an archaeology of personal protective equipment and its contribution to policy. (April 2021) - Schofield, John; Praet, Estelle; Townsend, Kathy A.; Vince, Joanna
Abstract: Abstract : The COVID-19 pandemic is creating a viral archive—an archaeological record of history in the making. One aspect of this archive is increased environmental pollution, not least through the discarded facemasks and gloves that characterise the pandemic. This article—directed specifically at archaeologists—argues that an archaeological perspective on 'COVID waste' using social media analysis can help to highlight environmental pollution, and that by giving this waste the status of archaeological material and working with other disciplines, archaeologists can contribute to sustainable, policy-led solutions to combat environmental pollution.